El apego como mediador de la relación entre el maltrato infantil y la sintomatología depresiva en la edad adulta: una revisión sistemática = Attachment as a mediator of the relationship between childhood maltreatment and depressive symptoms in adulthood : a systematic review - Sanz-Hortelano, Isabel (Revista de victimología, 2024)
Introduction. Considering its potential relevance for prevention and intervention with victims of childhood maltreatment, different studies have attempted to analyze the role of adult attachment in the relationship between child abuse and depressive symptoms. The aim of this study is to carry out a systematic review of the empirical literature with a robust methodology on the mediating role of attachment in the association between childhood maltreatment and depressive symptoms in the adulthood. Methodology. From the database and citation search, 13 articles were identified that met the inclusion and exclusion criteria. Results. Overall, the evidence confirms the mediating role of insecure attachment, although discrepancies are observed between the studies regarding the specific attachment dimensions that would act as mediators. Discussion. The type of childhood victimization experienced and the figure to whom the attachment evaluation is directed may be two determining variables in the effect of attachment on the association. Further studies are necessary to confirm the conclusions raised and serve as a basis for the design of more complete intervention programs for victims of child maltreatment.